Industry Attractiveness of Indian Comic Industry - Khandelwal, Anjeet (Indian Journal of Marketing, 2010)
The Corporate strategy of diversified companies (as different from business level strategy) has two major tasks: (i) the selection of the mix of businesses (i.e. the decision on the diversification strategy) and (ii) the value enhancing management of this mix of businesses based on appropriate organisational structures, systems and resource policies. There are two basic descriptive dimensions of corporate strategy - how diversified and how vertically integrated an organization is. It may be helpful to think of both of these dimensions as a continuum.